Food Counseling With Balanced Nutrition for Teenagers - Putra, Anak Agung Ngurah Dwi Ariesta Wijaya; Widnyani, Ida Ayu Putu Ary; Fitriani, Pande P. Elza (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institute Teknologi dan Kesehatan (ITEKES) Bali, 2021)
Nutritional knowledge plays an important role in shaping the mindset of choosing the type and amount of food consumed. A person with good nutritional knowledge is expected to pay attention to the nutritional state of each food he consumes. Unhealthy eating habits in choosing types of food can also have an impact on nutritional status problems. Nutritious food is not expensive and delicious food, but one that has a balanced nutritional value for the body. The food counseling with balanced nutrition for adolescents aims to provide information and knowledge to adolescents at SMK Erlangga. The result of this activity was that 96.39% of students understood the counseling material on balanced nutrition. This is good because it adds insight to students in order to find out optimal nutritional needs and improve daily eating patterns.